2020
DOI: 10.1186/s12902-020-00598-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between pulmonary function and albuminuria in type 2 diabetic patients with preserved renal function

Abstract: Background: Albuminuria is the early manifestation of the pathogenesis of diabetic nephropathy (DN). The current study was to investigate the relationship of pulmonary function with albuminuria in type 2 diabetic patients with preserved renal function to evaluate the role of pulmonary function in the early stage of DN. Methods: A total of 326 patients with type 2 diabetes mellitus (T2DM) including 270 without albuminuria and 56 with albuminuria, and 265 non-diabetic patients were enrolled. The patients' genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…Among T2D Chinese patients with preserved renal function (based on eGFR >60 mL/min/1.73m 2 ), low FEV 1 and low FVC were independently associated with albuminuria. 14 The current study among individuals with T2D with or without impairment in eGFR agrees with this previous finding. Conceivably, such associations could reflect the impact of primary lung disease with systemic manifestations (eg, COPD) on renal function.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Among T2D Chinese patients with preserved renal function (based on eGFR >60 mL/min/1.73m 2 ), low FEV 1 and low FVC were independently associated with albuminuria. 14 The current study among individuals with T2D with or without impairment in eGFR agrees with this previous finding. Conceivably, such associations could reflect the impact of primary lung disease with systemic manifestations (eg, COPD) on renal function.…”
Section: Discussionsupporting
confidence: 93%
“…Studies characterising the relationship between pulmonary and renal microvascular complications are limited. Among T2D Chinese patients with preserved renal function (based on eGFR >60 mL/min/1.73m 2 ), low FEV 1 and low FVC were independently associated with albuminuria 14. The current study among individuals with T2D with or without impairment in eGFR agrees with this previous finding.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Diabetic nephropathy is one of the most common microvascular complications, and the lung is a relatively microvascular and collagen-rich organ and therefore vulnerable to diabetic microangiopathy and histone nonglycosylation [ 2 , 8 ]. Alterations in microvascular ultrastructure regulate the thickening of the alveolar capillary endothelial cell matrix, which in turn affects pulmonary ventilation and pulmonary diffusion function [ 9 ]. Therefore, assessing pulmonary function in patients with DN can lead to better prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the National Health and Nutrition Examination Survey study of participants with chronic kidney disease showed that albuminuria was independently associated with obstructive and restrictive pulmonary function [ 7 ]. Furthermore, a study of 326 patients with type 2 diabetes mellitus revealed that renal dysfunction was associated not only with restrictive pulmonary function, but also with pulmonary diffusion function [ 8 ]. However, limited studies have confirmed the relationship between kidney and lung functions in the general population.…”
Section: Introductionmentioning
confidence: 99%